“A Feast of Languages”: The Role of Language in the Globe to Globe Festival - Kenny, Amy (Multicultural Shakespeare: Translation, Appropriation and Performance, 2014)
In 2012, Shakespeare’s Globe hosted the Globe to Globe Festival, which featured performances from thirty-seven international companies in their native tongues as part of the Cultural Olympiad in the lead up to the London Olympic Games. This paper explores the role that language played in the Globe to Globe Festival, and the way in which language mediated direction and translation of various plays, specifically in the rehearsal room in anticipation of the performance itself. Translating Shakespeare into thirty-seven different languages allowed the companies to think about the potential benefits of performing their play in a specific dialect or style for both audiences at the Globe and their own language and culture as well. This paper considers the impact of language barriers that existed even within individual companies, and shows that the specific choices around language informed the ways audience members understood and interpreted the narratives of the plays during the festival.